Efficacy of Dialectical behaviour Techniques (DBT) in Reduction of Anxiety of Students in Tehran- Iran - Shahrbanoo Ghahari (Journal of Global Pharma Technology, 2017)
Background and objective: Dialectical Behavior Therapy techniques can be used as useful and effective method in reduction of many clinical symptoms. In this study, Efficacy of dialectical behavior therapy in reduction of   anxiety of students in Tehran City is investigated. Methods and materials: this study is in kind of empirical study with pretest and posttest design with control group. Statistical population in this study consists of all high school female students of Tehran (n=674) educating during academic year of 2015-2016. First, cluster sampling is used and 4 schools are selected from schools of Tehran and from each couple of schools, 2 classrooms were selected and the students with high score in Beck's Anxiety Inventory (BAI) were selected as sample. Then, 30 students were selected using random sampling method and were placed in two groups with 15 people in each group. Both groups fulfilled the BAI in basic step. Experimental group received 12 sessions’ intervention with dialectical behavior therapy techniques and control group remained in waiting list. Both groups fulfilled BAI again after the treatment. Obtained data are analyzed using MANCOVA. Results: obtained results from the study showed that Dialectical Behavior Therapy can affect reduction of anxiety of female students and mean values of both groups are significantly different from each other (p<0.01).Conclusion: Dialectical Behavior Therapy (DBT) techniques can lead to reduction of anxiety of female students.Keywords: Dialectical behavior therapy (DBT) techniques, Anxiety, Female students.